Attitudinal parity among competing brand consumers - Vargas Bianchi, Lizardo (2022)
The paper argues that advertising messages are not capable of mediating brand choice through its effect on consumers' attitudes towards an advertised product. In stead, it suggests the similarity between overall attitudinal indexes seen in competing brands' consumers, phenomenon that might found its origin in the functional parity observed within fast moving consumer good categories, as well as in the knowledge consumers have of those goods. These markers have implications in the planning and practice of marketing communications.